How do supermarkets and discounters communicate about sustainability? A comparative analysis of sustainability reports and in-store communication. Issue 11 (11th November 2019) - Saber, Marcus; Weber, Anja
Abstract : Purpose: Commonly, supermarkets are perceived as more sustainable than discount stores, which are accused of following an aggressive price and no-frills approach. Therefore, the purpose of this paper is to investigate whether supermarkets and discounters differ substantially in their sustainability communication. Design/methodology/approach: Sustainability reports and in-store communication are two important channels for retailers' sustainability communication. To analyze both communication channels, the authors use a multi-method approach with data triangulation, analyzing sustainability reports and store observations of eight German retailers (two supermarket chains, six discount chains). Findings: The study reveals no major differences between supermarkets and discounters regarding the readability of sustainability reports and the number of key figures on sustainability presented. However, supermarkets perform significantly better in translating sustainability to the store level than discounters. Furthermore, the results indicate that poor quality in the readability analysis is reflected in fewer concrete data provided in the sustainability reports and poorer translation of sustainability to the retail store. Originality/value: This paper presents an empirical analysis of how well German retailers communicate about sustainability on both the report and the store level for the interest of academia and retail managers. It reveals different performance qualities among retail chains and retail formats and identifies the shortcomings within current reporting legislation with a clear indication toward policy makers.